1) 4*(x+3) = 4x+4*3 = 4x+12
2) 3*(x+8) = 3x+24
3) 2*(7-a) = 14-2a
4) 5*(p-10) = 5p-50
5) 6*(a-2b) = 6a-12b
6) (m+3n)*4 = 4m+12n
7) 2*(3x-2y)*3 = 6*(3x-2y) = 18x-12y
8) 3*(2p-5q)*7 = 21*(2p-5q) = 42p-105q
1) (x+y)*a = ax+ay
2) b*(x-y) = bx-by
3) 3x*(2a+b) = 6ax+3bx
4) 2y*(3x-y) = 6xy-2
5) 5x*(6x+3y) = 30+15xy
6) 3a*(-4b-2a) = -12ab-6
7) -6a*(5b-2a) = -30ab+12
8) 8m*(m+n) = 8+8mn
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
1) 4*(x+3) = 4x+4*3 = 4x+12
2) 3*(x+8) = 3x+24
3) 2*(7-a) = 14-2a
4) 5*(p-10) = 5p-50
5) 6*(a-2b) = 6a-12b
6) (m+3n)*4 = 4m+12n
7) 2*(3x-2y)*3 = 6*(3x-2y) = 18x-12y
8) 3*(2p-5q)*7 = 21*(2p-5q) = 42p-105q
1) (x+y)*a = ax+ay
2) b*(x-y) = bx-by
3) 3x*(2a+b) = 6ax+3bx
4) 2y*(3x-y) = 6xy-2
5) 5x*(6x+3y) = 30+15xy
6) 3a*(-4b-2a) = -12ab-6
7) -6a*(5b-2a) = -30ab+12
8) 8m*(m+n) = 8+8mn